Problematika Pendidikan Islam di Indonesia: Eksplorasi Teori Motivasi Abraham Maslow dan David McClelland - Nanang Hasan Susanto; Cindy Lestari (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2018)
This paper aims to offer a comprehensive idea for one of the issues of Indonesia’s education, particularly in Islamic education. The issues deal with low student achievement as well as the phenomenon of teacher situated in a mechanistic curriculum, through motivation theories proposed by Abraham Maslow and David McClelland. A qualitative approach was designed in this library research. The study employed discourse analysis and cultural analysis as the methods of data analysis regarding the reality of Indonesia’s education. This study promotes the urgency of enhancing students’ motivation in experiencing Islamic education, either by fulfilling five basic needs as suggested in the Maslow’s theory or by fostering need for achievement (nAch) as portrayed in the McClelland’s theory, to explore the national education problems. This study depicts that motivation constitutes the main factor that significantly contributes to students’ achievement. It, likewise, denotes the students’ abilities in developing learning materials through their creativity and innovations in terms of their own potential, specifically for Islamic education